Environmental Hazards of Chemical Pollution: Assessments and Mitigation - Theeranat Suwanaruang (Environmental Hazards of Chemical Pollution: Assessments and Mitigation, 2024)
"Environmental Hazards of Chemical Pollution: Assessments and Mitigation" thoroughly investigates the complex effects and management of dangerous chemicals on human health and ecosystems. After providing an overview of environmental chemistry, the book explores the origins, characteristics, and actions of dangerous substances found in soil, water, and air. It addresses the risks to both acute and chronic health by analyzing their effects on ecosystem resilience, biodiversity, and human populations. Effective risk assessment, management, and sustainable practices are crucial, as demonstrated by international agreements, case studies of notable incidents, and regulatory frameworks. The book explores new developments in green chemistry, emerging technologies, and how chemical safety fits into the larger picture of global sustainability. It also makes the case for teamwork in reducing chemical risks in the future and securing a more sustainable and safe future.